Use of defective interfering particle RNA probes in the determination of the order of in vitro transcription of vesicular stomatitis virus genes. - Reddy, D V (1977)
Annealing of various defective interfering particle RNAs of vesicular stomatitis virus to early in vitro viral transcription products has shown that transcription is sequential, with 13S to 18S mRNA's being produced first. Based on this finding, the 30S mRNA cistron is located at the 5' end of the viral genome.